Evaluation and Enhancement of Triaging Services Through Quality Improvement Tools at Primary Health Care Level: A Clinical Audit Study - Ansif Pallath Majeed; Noora Alkubaisi; Kiran Harikumar; Hanan Al Mujalli; Abdul Ali Shah; Sharifullah Khan; Soraimah Sarip Socor (SAGE Publishing, 2023)
Background: The effective and efficient operation of emergency services at healthcare depends on triage decisions. Successfully implementing a triage system improves patient care, communication, and self-assurance. Methods: A baseline audit was conducted by reviewing a sample of 554 triage health records in September 2021. Many gaps were identified in the practice, and action plans were developed for improving it. Following the implementation of the action plan, a re-audit was conducted in September 2022 with a sample of 470 medical records. Results: Evidence suggested that nurses had made progress in correctly allocating the medical emergency triage category from 63% at baseline to 90% at the reaudit. The over-triage decreased in accordance with this adjustment, from 37% to 10%. Compliance with the suggested time target of 5 minutes for physicians to attend medical emergencies has shown a small improvement from 48% at baseline to 55% in the re-audit. Similar improvements were demonstrated in the other triage categories. Conclusion: A problem may have several causes, and since it is impossible to address every one of them, prioritizing the causes is usually the best course of action. Inadequate triage classification by nurses was one of the key reasons for the delay in physician appointment times in triage clinics. Triage nurses' abilities should be enhanced to make this triage judgment. The audit team suggested that nurses should be given problem-based training, which will enhance the entire triage procedure.